An autonomous unmanned aerial vehicle for inspecting and supplying emergency kits at a spot of casualty in water ways - Ahad, Muntasir; Lamim, Lubaina Haque; Shamonti, Nafisa Rahman; Arnab, Shams Fardous (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.